An Organofluorine Isoselenocyanate Analogue of Sulforaphane Affects Antimetabolite 5-Fluorouracil’s Anticancer Activity: A Perspective for New Combinatory Therapy in Triple-Negative Breast Cancer - Małgorzata Milczarek; Tomasz Cierpiał; Piotr Kiełbasiński; Milena Małecka-Giełdowska; Marta Świtalska; Joanna Wietrzyk; Maciej Mazur; Katarzyna Wiktorska (Molecules, 2023)
Antimetabolites, especially 5-fluorouracil, are commonly used clinically to treat breast, colon, and other cancers. However, their side effects and inefficiency in monotherapy have prompted further searches for new combinations. Thus, the anticancer effect of 5-fluorouracil (5-FU) and the sulforaphane analogue, 4-isoselenocyanato-1-butyl 4′-fluorobenzyl sulfoxide (ISC), were tested in in vitro and in vivo models of triple-negative breast cancer (TNBC) as a new option for this treatment-resistant and aggressive type of breast cancer. A synergic interaction between 5-FU and ISC was observed in the TNBC in vitro model MDA-MB-231 cell line, which led to enhanced antiproliferative effects. The results of in vitro studies were confirmed by in vivo tests, which demonstrated stronger tumor growth inhibition and additive interactions between 5-FU and ISC in the murine TNBC model. Moreover, the results of the body mass and blood analysis showed the safety of the tested combination. The mechanistic study revealed that the combined treatment triggered apoptosis and necrosis, as well as inhibited cell migration.